Attitude towards student eachers and some related cognitive factors perception of teaching style, perception of rewards and evaluation of teaching performance. - Llanzana, Donna Kristina Omani
The study sought to demonstrate the attitude towards student teachers of fourth-year highs school student and its relationship to some related cognitive factors: the perception of teaching style, perception of rewards and evluation of teaching performance. The study was conducted to 100 senior high school students of Pototan National Comprehensive High School in Pototan., The design of this study was descriptive-correlational. Scales were used to measure the variables of the study. these were the Attitude Scale Towards Student Teachers developed by Shaw and Wright, (1967); The Perception Scale of the Student Teachers' Teaching Style developed by Grasha (1994); the Perception of Rewards Scale, which was developed by the researchers; and the Teaching Performance Evaluation Scale which is based from the UP Faculty Evaluatio Instrument. Data were analyzed using the spearman Rank Order Correlation. Analysis showed that the general attitude of PNCHS, senior high school students were related to their perception of the student teachers' teaching style and their evaluation of the student teachers' teaching performance but there is no significant relation found between their attitude towards student teachers and percpetion of rewards (p> 0.05).